A study of critical rainfall and landslide occurrence - Gupta, S.; Leong, E.C. (Japanese Geotechnical Society Special Publication, 2019)
Landslide hazards have caused loss of human lives, failure of structures, damage to agricultural lands and the natural environment. Rainfall-induced landslides constitute a major proportion of landslides in different parts of the world. Efforts are make to understand the mechanism that triggers landslide due to rainfall. One often cited trigger factor of rainfall-induced landslides is critical rainfall. The critical rainfall can vary in duration from 1 hour to antecedent rainfall of several days. However, such critical rainfall is obtained from observation at a particular location and may not be used or extrapolated to other locations. This paper collates case studies of rainfall-induced landslides that occurred in different parts of the world. Information collated includes location, soil type, permeability, slope angle, slope height, average annual rainfall of that area and the critical rainfall responsible for the landslide. The relationships between critical rainfall and other variables are examined critically. The study found that only soil type, slope angle and critical rainfall were useful. The study shows that 1-hour and 1-day critical rainfall increases with slope angle. It appears that the critical rainfall has an exponential relationship with slope angle. For coarse-grained soils, the 1- hour critical rainfall exponential relationship with slope angle can be used as the trigger rainfall for slope failures. For fine-grained soils, the 1-day critical rainfall exponential relationship with slope angle can be used as the trigger rainfall for slope failures. However, the findings are based on limited case studies. These relationships should be further validated with more case studies. © 2019 7th Asia-Pacific Conference on Unsaturated Soils, AP-UNSAT 2019. All rights reserved.
Keywords: Critical rainfal; Landslides; Rainfall threshold; Slope failure